ChemInform Abstract: A Unified Stereodivergent Strategy for Prostaglandin and Isoprostanoid Synthesis. Issue 36 (9th September 2014) - Valli, Matteo; Chiesa, Francesco; Gandini, Andrea; Porta, Alessio; Vidari, Giovanni; Zanoni, Giuseppe
Abstract Starting from compound (III) important key intermediates for prostaglandin and isoprostanoid syntheses are prepared.